1993
DOI: 10.1099/00221287-139-11-2811
|View full text |Cite
|
Sign up to set email alerts
|

Periodic selection in longterm continuous-flow cultures of the filamentous fungus Fusarium graminearum

Abstract: By monitoring increases and decreases in the proportion of cycloheximide-resistant macroconidia, periodic selection was observed in populations of the filamentous fungus Fusarium graminearurn, grown in glucose-limited chemostat cultures. The results indicated that periodic selection of advantageous mutants of F. graminearurn occurred at intervals of about 124 h at both high (D = 0.19 h-', approximately 34 generations) and low (D = 0-06 h-', approximately 11 generations) dilution rates. Several 'adaptive' peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Dykhuizen and Hartl13 showed this to be the case by numerical simulation. Wiebe et al 42 used a similar analysis to investigate the selection and origin of colonial mutants of the filamentous fungus Fusarium grarninarium during chemostat culture.…”
Section: Determination Of Selection Coefficients and Origin Of Mutantsmentioning
confidence: 99%
“…Dykhuizen and Hartl13 showed this to be the case by numerical simulation. Wiebe et al 42 used a similar analysis to investigate the selection and origin of colonial mutants of the filamentous fungus Fusarium grarninarium during chemostat culture.…”
Section: Determination Of Selection Coefficients and Origin Of Mutantsmentioning
confidence: 99%
“…A major problem in the use of continuous cultures is the rapid appearance of morphological mutants, often leading to a reduction in protein production and altered growth characteristics (Christensen et al, 1995;Mainwaring et al, 1999;Wiebe et al, 1994;Withers et al, 1998). The mutants were affected in sporulation, branching, or both Wiebe et al, 1993;Withers et al, 1995) and were often demonstrated to have a selective advantage over the parental strain. Also, nonmorphological mutations with altered production characteristics may occur (Mainwaring et al, 1999;Pederson et al, 2000;Wiebe et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In glucose-limited chemostat culture, the interval between the onset of continuous flow and the first (adaptive) peak of cycloheximide-resistant macroconidia was longer (384 h) for A23-S than that observed in the parental strain (longest interval = 171 h, Wiebe et a/., 1993), suggesting that the former culture was more homogenous at the onset of continuous medium flow than the latter. Similarly, a long first interval before the first (adaptive) peak of cycloheximide-resistant macroconidia was observed in both A24-S fermentations.…”
Section: Competition Between A3/5 A22-1 and A23-smentioning
confidence: 91%
“…Fluctuations in the concentration of cycloheximideresistant macroconidia were monitored during the first A24-S experiment and seven peaks of cycloheximide were observed (data not shown). After the first interval, which lasted about 336 h or 87 generations, the average interval between peaks in the concentration of cycloheximide-resistant macroconidia was 208 f 28 h or about 54 generations, and was significantly ( P < 0.05, t-test) longer than the intervals observed for either the A3/5 (Wiebe et a/., 1993) or the A23-S chemostat populations (124 f 12 h and 160 f 12 h, respectively).…”
Section: Appearance Of Colonial Mutants and Periodic Selection In A24mentioning
confidence: 99%